Penyuluhan dan Edukasi Fisioterapi tentang Cegah Masalah pada Ibu Hamil di Puskesmas Lolo Kalimantan Timur - Nadhila Khairunisa; Dimas Sondang Irawan; Herlina Herlina (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
Introduction: Pregnancy is a natural process that every woman experiences. During pregnancy, pregnant women experience many changes, both physiological and psychological. These changes can cause various symptoms in each pregnant woman. Some common complaints during pregnancy include nausea and vomiting, back pain, edema, and shortness of breath. Method: This activity was conducted through counseling aimed at explaining the condition and understanding it to pregnant women. This activity used leaflets and live demonstrations so that participants could perform exercises correctly. Conclusion: After conducting counseling on the role of physiotherapy in pregnancy problems at the integrated health posts (Posyandu) for pregnant women in Sempulang Village, Janju Village, and Keluang Lolo Village, it can be concluded that education is important regarding understanding good exercises to do during pregnancy, such as child pose, cat and camel exercise or yoga for pregnant women, and breathing exercises. This is useful for reducing and preventing symptoms during pregnancy by always paying attention to signs of when to stop the exercise.